Translation norms in the light of practical research in literary translation - Enríquez-Aranda , Mercedes (Onomázein, 2016)
The study of translation norms is presently developed within the framework that relates translation to social, power and ideological aspects. Linked to both Linguistics and Sociolinguistics, norms are understood as the formulation of the values shared by a community in a certain situation. Thus they are psychological and social entities that have a social control function. From this point of view, translation norms are recurrent rules of behaviour that govern, identify and individualize the social order of the cultural system where translation takes place. The translation behaviour is then considered a communicative and a social practice. In this article, a brief review of the current state of the art of the theoretical reflection on translation norms is offered, followed by a practical study of the Spanish translations of John Keats’s odes and sonnets included in isolated editions published in Spain in the 20th century. Normative translator behaviours find a definition, which allows a classification of translations according to the natural evolution of the socio-cultural context where translations are produced and received. Conclusions can be extrapolated to the study of the most common practices followed nowadays in the translation of poetry in Spain.